Coordinating a supplier–retailer JELS model considering product quality assessment and green retailing. (1st July 2022) - Sarkar, Sumon; Modak, Nikunja Mohan; Giri, Bibhas C.; Sarkar, Ashis Kr.; Cárdenas-Barrón, Leopoldo Eduardo
Abstract: Environmental awareness among the people is constantly increasing, which has resulted in massive pressure on companies from various stakeholders including the government and consumers to mitigate the detrimental effects on the environment. This work deals with a joint economic lot size (JELS) model to enhance the greening efforts of a product that flows along a two-level supply chain (supplier–retailer). Both selling price and greening effort level of the product influence the market demand. Here we assume that every individual lot shipped to the retailer carries some random defective items. Each lot received by the retailer goes through an error-free sub-lot sampled inspection process to remove the defective items. A fraction of faulty items are classified as usable and are sold at a salvage value and the rest items are disposed of. The retailer has to bear per item penalty cost for selling the uninspected defective items. We develop the profit function under three decision-making scenarios: centralized, decentralized, and coordinated. Coordination is made based on a trade-credit scheme under which the retailer changes his/her optimal decisions according to a centralized policy. We obtain a minimum and maximum credit period duration which encourages both the retailer and the supplier to follow the coordinated decision-making policy. The coordinated model suggests that more emphasis should be given to the greening effort level for higher profit. It is observed that, in many cases, a sub-lot inspection gives better results compared to a full lot inspection. Highlights: A single supplier–single retailer sustainable supply chain is considered. Both selling price and greening level has influence on market demand. Every batch contains some defective items and hence a sub-lot sampling inspection policy is considered. Coordination is made based on trade credit scheme. Extensive numerical experiments are carried out and managerial insights are drawn.